2018
DOI: 10.3390/universe4080088
|View full text |Cite
|
Sign up to set email alerts
|

The Case for Nonlocal Modifications of Gravity

Abstract: Abstract:The huge amounts of undetected and exotic dark matter and dark energy needed to make general relativity work on large scales argue that we should investigate modifications of gravity. The only stable, metric-based and invariant alternative to general relativity is f (R) models. These models can explain primordial inflation, but they cannot dispense with either dark matter or dark energy. I advocate nonlocal modifications of gravity, not as new fundamental theories but rather as the gravitational vacuu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 142 publications
0
33
0
Order By: Relevance
“…In this paper we will only consider analytic form-factors. However, it is worth mentioning that nonlocal models with nonanalytic differential operators have been investigated by many authors; see, for example, Refs [59][60][61][62][63][64]…”
mentioning
confidence: 99%
“…In this paper we will only consider analytic form-factors. However, it is worth mentioning that nonlocal models with nonanalytic differential operators have been investigated by many authors; see, for example, Refs [59][60][61][62][63][64]…”
mentioning
confidence: 99%
“…Nonlocal effective gravitational actions have very interesting cosmological phenomenology such as explaining problems of dark matter [52], dark energy [52,53] and inflation [54]. It has quite unusual classical features [55,56]. A comprehensive review of its quantum properties can be found in [57].…”
Section: (): V-volmentioning
confidence: 99%
“…The justification for nonlocality comes from quantum field theory, in which nonlocality inevitably arises as quantum loop corrections of massless particles; see, for example [23]. It has been suggested that a nonlocal quantum effective action might derive from fundamental theory through the gravitational vacuum polarization of infrared gravitons vastly produced during primordial inflation [24,25]. However, since no such derivation is currently available, one may take a phenomenological approach, that is to guess what form of nonlocal actions would do the job of generating an accelerated expansion without dark energy [26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%